Empathy and Ethics: The Role of Character Growth in Literature - Alkubaisi, Asst. Prof. May Hasan Srayisah Alkubaisi (Sulaimani Journal for Humanities, 2026)
Literature has long served as a mirror to society, reflecting its values, beliefs, and moral dilemmas. Modern stories, in particular, encapsulate the complex moral lessons within their concise narratives. This study explores the relationship between empathy and ethical growth through the development of the character of an Arab woman in the story of Zahra: Strength of an Arab Woman by Ghada Gad. It posits that well-crafted characters in literary works serve as conduits for readers to engage with complex moral dilemmas, fostering empathetic understanding and ethical reflection. This research examines how character arcs and interpersonal relationships shape readers’ emotional responses and moral reasoning by analysing diverse literary scripts. Through a qualitative approach that includes textual analysis and reader surveys, the study aims to demonstrate that exposure to rich character development enhances empathy and contributes significantly to moral growth. The findings will provide valuable insights for educators and literature enthusiasts on the transformative power of storytelling, highlighting its potential to cultivate empathy and ethical awareness in contemporary society. Ultimately, this research underscores the vital role of literature in promoting moral development and encourages further exploration of its impact on readers' values and behaviours.
Keywords: Ghada Gad; Zahra; Character Growth; Empathy; Ethical Development